Effect Of Vitamin D3 On Transforming Growth Factor - Β1 In Pediatric Patients With Stage 1 To 3 Chronic Kidney Disease: An Experimental Study And Randomized Controlled Trials - Krisni Subandiyah; Richi Aditya (Pediatric Sciences Journal, 2022)
Introduction: In Indonesia, Chronic Kidney Disease (CKD) is a severe health problem both in terms of treatment and health costs. One way to reduce mortality is by blocking the progression of the disease. Transforming Growth Factor-β1 (TGF-β1) is a marker of progression from CKD through its fibrosis pathway. One mechanism for interfering with the TGF-β1 signaling pathway is by giving vitamin D3(cholecalciferol). This study aims to find out that supplementation of vitamin D3 can increase plasma 25(OH)D levels and reduce TGF-β1 levels in children with CKD. Methods: The study was approved by the hospital's ethical committee, designed as a randomized clinical trial, double-blind, pre and post-test control group, which involved 30 subjects diagnosed as CKD stage 1-3. Subjects were divided into two groups; the vitamin D3-treated group and the placebo group. TGF-β1 and vitamin D plasma level was measured by ELISA method. Results: Vitamin D levels increased by 9.35 compared to the placebo group. The magnitude of the increase from the Wilcoxon statistical test results obtained p=0.001 (p<0.05), so there was a significant increase in vitamin D levels after supplementing vitamin D3. In the group given vitamin D3 supplementation, it was found that TGF-β1 levels had decreased by 108.64. The reduction from the Wilcoxon statistical test results obtained p=0.001 (p<0.05), so there was a significant decrease after vitamin D3 supplementation. Based on the Spearman correlation test, there is a meaningful relationship between increased vitamin D levels with a reduction of TGF-β1 levels. The correlation coefficient is -0.753, which is harmful. The correlation coefficient is in a substantial range. Conclusion: We concluded that vitamin D3 could increase 25(OH)D plasma level and decrease TGF-β1 levels significantly in children with stage 1 until 3 of CKD.